2009
DOI: 10.1002/app.29660
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of soy hull‐reinforced biocomposites from conjugated soybean oil

Abstract: The tensile and flexural properties of new thermosetting composites made by the free radical polymerization of a conjugated soybean oil (CSO)-based resin reinforced with soy hulls have been determined for various resin compositions. The effects of reinforcement particle size and filler/resin ratio have been assessed. The thermal stability of the new materials has been determined by thermogravimetric analysis and the wt % of oil incorporation has been calculated after Soxhlet extraction (the extracts have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
68
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 28 publications
10
68
2
Order By: Relevance
“…It has also been shown that when vegetable oils are cationically co-polymerized with mixtures of DVB and ST, a homogeneous material is obtained [4]. In a related work, evaluating the concentration of DVB in conjugated vegetable oil-based resins cured by free radical polymerization, it has been shown that samples containing 15 wt % of DVB exhibit good mechanical properties [5]. In the current work, preliminary tests with a range of concentrations of tung oil and ST, showed that the resins containing 70 wt % of tung oil, 15 wt % of DVB, 10 wt % of ST, 3 wt % of soybean oil, and 2 wt % of BF3·OEt2 exhibit a gellation time of 30 min at room temperature.…”
Section: Resin Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that when vegetable oils are cationically co-polymerized with mixtures of DVB and ST, a homogeneous material is obtained [4]. In a related work, evaluating the concentration of DVB in conjugated vegetable oil-based resins cured by free radical polymerization, it has been shown that samples containing 15 wt % of DVB exhibit good mechanical properties [5]. In the current work, preliminary tests with a range of concentrations of tung oil and ST, showed that the resins containing 70 wt % of tung oil, 15 wt % of DVB, 10 wt % of ST, 3 wt % of soybean oil, and 2 wt % of BF3·OEt2 exhibit a gellation time of 30 min at room temperature.…”
Section: Resin Compositionmentioning
confidence: 99%
“…In such systems, the reactive sites in the triglyceride units are the carbon-carbon double bonds along the fatty acid chains. Overall, the reactivity of vegetable oils towards these polymerization processes is significantly higher when the carbon-carbon double bonds are conjugated [5]. Furthermore, the higher the degree of unsaturation of an oil, the higher the crosslink density of its resulting co-polymer, and the better its mechanical properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the preparation of such materials, it has been demonstrated that free radical initiators are quite effective in crosslinking the carbon–carbon double bonds in the oils and the other monomers used. The presence of ligno‐cellulosic filler particles minimizes shrinkage of the resin and only minimal microcracks have been detected by scanning electron microscopy (SEM) of soybean hull composites 30. Recent results from the study of natural filler‐reinforced composites in the Larock group suggested that maleic anhydride (MA) can serve as a good filler‐resin compatibilizer and help improve the stress transfer from the matrix to the reinforcement, resulting in an overall increase of the mechanical properties 32, 33…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The green composites produced in our group have used a range of agricultural fibers to strengthen biobased resins prepared by the free-radical copolymerization of conjugated vegetable oils through the carbon-carbon double bonds present in the triglyceride. Spent germ, 15 the coproduct of wet-mill ethanol production, soybean hulls, 16 corn stover (CS), 17 and wheat straw (WS) 18 have all been used to reinforce resins based on tung oil, conjugated soybean oil (CSOY), or conjugated linseed oil (CLIN). In this study, we also used CS, WS, and switchgrass (SWG) as natural fiber reinforcements but instead focused on resins produced by the cationic copolymerization of conjugated natural oils, such as corn, soybean, fish, and linseed oils.…”
Section: Introductionmentioning
confidence: 99%